Novel route for rapid biosynthesis of lead nanoparticles using aqueous extract of Jatropha curcas L. latex - Joglekar, Shriram; Kodam, Kisan M.; Dhaygude, Mayur; Hudlikar, Manish (Materials Letters, 2011)
We are reporting a novel, low-cost and eco-friendly route for rapid synthesis of lead nanoparticles by using 0.5% aqueous extract of Jatropha curcas L latex. Lead nanoparticles were characterized initially by UV-vis spectroscopy and shown distinct peak at 218 nm. This peak was highly specific for lead nanoparticles. Formation of Pb (0) was confirmed by X-ray diffraction technique (XRD).Transmission electron microscopy (TEM) was performed for estimating the size and shape of nanoparticles. The average size of lead nanoparticles was found to be in the range of 10 to 12.5 nm. Energy dispersive analysis of X-rays (EDAX) showed distinct peaks of lead. Fourier Transform Infrared Spectroscopy (FTIR) were performed to find the role of cyclic peptides namely curcacycline A (an octapeptide) and curcacycline B (a nonapeptide) as a possible reducing and capping agents present in the latex of Jatropha curcas L. Lead nanoparticles formed by the above method were monodisperse. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: FTIR; Latex; Lead nanoparticles; Nanoparticles

Green synthesis of TiO2 nanoparticles by using aqueous extract of Jatropha curcas L. latex - Hudlikar, Manish; Joglekar, Shriram; Dhaygude, Mayur; Kodam, Kisan M. (Materials Letters, 2012)
Present study deals with a green synthesis of TiO2 nanoparticles by using 0.3% aqueous extract prepared from latex of Jatropha curcas L. TiO2 nanoparticles were characterized by X-ray diffraction (XRD), Selected Area Electron Diffraction (SAED), Transmission Electron Microscopy (TEM), Energy Dispersive Analysis of X-rays (EDAX) and Fourier Transform Infrared Spectroscopy (FTIR). Fourier Transform Infrared Spectroscopy (FTIR) were performed to find the role of curcain (enzyme), cyclic peptides namely curcacycline A (an octapeptide) and curcacycline B (a nonapeptide) as a possible reducing and capping agents, present in the latex of J. curcas L. The average size of TiO2 nanoparticles was found to be in the range of 25 to 100 nm. Our result shows that there are two broad categories of nanoparticles, first having diameter from 25 to 50 nm which are mostly spherical in shape and second having some larger and uneven shapes. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Electron microscopy; Fourier Transform Infrared Spectroscopy (FTIR); Nanostructures

Latex-mediated synthesis of ZnS nanoparticles: green synthesis approach - Hudlikar, Manish; Joglekar, Shriram; Dhaygude, Mayur; Kodam, Kisan M. (Journal of Nanoparticle Research, 2012)
A low-cost, green synthesis of ZnS nanoparticles is reported using 0.3 % latex solution prepared from Jatropha curcas L. ZnS nanoparticles were characterized by X-ray diffraction, selected area electron diffraction, transmission electron microscopy, energy dispersive analysis of X-rays, UV-vis optical absorption and photoluminescence techniques. Fourier Transform Infrared Spectroscopy was performed to find the role of cyclic peptides namely curcacycline A (an octapeptide), curcacycline B (a nonapeptide) and curcain (an enzyme) as a possible reducing and stabilizing agents present in the latex of J. curcas L. The average size of ZnS nanoparticles was found to be 10 nm. Latex of J. curcas L. itself acts as a source of sulphide (S-2) ions that are donated to Zn ions under present experimental conditions. Source of sulphide (S-2) ions is still unclear, but we speculate that cysteine or thiol residues present in enzyme curcain may be donating these sulphide (S-2) ions.
Keywords: green synthesis; Latex; ZnS nanoparticles

Novel route for rapid biosynthesis of copper nanoparticles using aqueous extract of Calotropis procera L. latex and their cytotoxicity on tumor cells - Harne, Shrikant; Sharma, Ashwinikumar; Dhaygude, Mayur; Joglekar, Shriram; Kodam, Kisan M.; Hudlikar, Manish (Colloids and Surfaces B-Biointerfaces, 2012)
This paper accounts for novel, low-cost, eco-friendly route for rapid biosynthesis of copper nanoparticles. Cysteine proteases present in the latex of Calotropis procera L. were used to fabricate copper nanoparticles from copper acetate. Copper nanoparticles were initially characterized by transmission electron microscopy (TEM) and X-ray diffraction technique (XRD). Transmission electron microscopy (TEM) was used to estimate the size and shape of nanoparticles. The average size of copper nanoparticles was found to be 15 +/- 1.7 nm. Energy dispersive analysis of X-rays (EDAX) showed distinct peaks of copper. Fourier transform infrared spectroscopy (FTIR) was performed to confirm capping behavior of the latex proteins that contributed to long term stability of copper nanoparticles (6 months) in aqueous medium. Copper nanoparticles synthesized by above method were monodisperse type. Cytotoxicity studies of latex stabilized copper nanoparticles were carried out on HeLa, A549 and BHK21 cell lines by MTT dye conversion assay. HeLa, A549 and BHK21 cells showed excellent viability even at 120 mu M concentration of copper nanoparticles. This shows that copper nanoparticles synthesized by above method hold excellent biocompatibility. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biocompatible; Copper nanoparticles; FTIR; Latex; Tumor cells; X-ray diffraction technique (XRD)